Channel-mediated ATP release in the nervous system. (1st April 2023) - Dale, Nicholas; Butler, Jack; Dospinescu, Valentin-Mihai; Nijjar, Sarbjit
Abstract: ATP is well established as a transmitter and modulator in the peripheral and central nervous system. While conventional exocytotic release of ATP at synapses occurs, this transmitter is unusual in also being released into the extracellular space via large-pored plasma membrane channels. This review considers the channels that are known to be permeable to ATP and some of the functions of channel-mediated ATP release. While the possibility of ATP release via channels mediating volume transmission has been known for some time, localised ATP release via channels at specialised synapses made by taste cells to the afferent nerve has recently been documented in taste buds. This raises the prospect that "channel synapses" may occur in other contexts. However, volume transmission and channel synapses are not necessarily mutually exclusive. We suggest that certain glial cells in the brain stem and hypothalamus, which possess long processes and are known to release ATP, may be candidates for both modes of ATP release -channel-mediated volume transmission in the region of their somata and more localised transmission possibly via either conventional or channel synapses from their processes at distal targets. Finally, we consider the different characteristics of vesicular and channel synapses and suggest that channel synapses may be advantageous in requiring less energy than their conventional vesicular counterparts. This article is part of the Special Issue on "Purinergic Signaling: 50 years". Graphical abstract: Image 1 Highlights: ATP can be released from cells via different species of large-pored ion channel. Several different types of stimuli can open these ATP-releasing channels. ATP released via channels mediates both volume and synaptic transmission. We discuss functional examples of channel-mediated ATP release in nervous system. We propose potential advantages of channel-mediated versus exocytotic ATP release.